Design of a robust neural network controller for inverted pendulum - Li, Jijun. (2008)
Control system has a long and distinguished tradition stretching back to the 19th-century dynamics and stability theory. Since 1950s, quite unparalleled developments in the underlying theory with applications ranging from the ubiquitous PID controller, widely encountered in the process industries, through to high-performance fidelity controllers typical of aerospace applications. With the support by computing hardware and software, an intense research effort is being directed to the development of high-performance controllers which are robust to specified classes of plant uncertainty.